2002
DOI: 10.1071/sr01087
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification in a Vertisol subsoil and its relationship to the accumulation of ammonium-nitrogen at depth

Abstract: Unusually high concentrations of ammonium have been observed in a Vertisol below 1 m depth in south-east Queensland. This study investigated the possibility that an absence of nitrification is allowing this ammonium to accumulate and persist over time, and examined the soil environmental characteristics that may be responsible for limiting nitrifying organisms. The possibility that anaerobiosis, soil acidity, soil salinity, low organic carbon concentrations, and/or an absence of active nitrifying microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Zhu and Ehrenfelc (1999) found that soils with higher plant root biomass had more chances to occur nitrification. Page et al (2002) reported that nitrifying organisms were likely to be absent in the subsoil due to inhibition of high alkalinity of subsoils (pH=9.0). Hence high NH þ 4 À N contents in deep soil depths were most likely caused by less plant uptake and nitrification.…”
Section: Resultsmentioning
confidence: 98%
“…Zhu and Ehrenfelc (1999) found that soils with higher plant root biomass had more chances to occur nitrification. Page et al (2002) reported that nitrifying organisms were likely to be absent in the subsoil due to inhibition of high alkalinity of subsoils (pH=9.0). Hence high NH þ 4 À N contents in deep soil depths were most likely caused by less plant uptake and nitrification.…”
Section: Resultsmentioning
confidence: 98%
“…5). Highly mobile ions, such as NO 3 -, have been shown to concentrate deeper within the soil profile (Thomas et al 1995;Turpin et al 1998) concentration of NH 4 + has also been reported between soil depths of 1.2 and 3 m; however, in some Vertosols, the source of this deposit is unknown (Page et al 2002).…”
Section: Subsoil Nutrient Deficienciesmentioning
confidence: 99%
“…Brigalow (Acacia harpophylla), an N 2 -fixing tree species, tends to overlay acidic subsoils (Ahern et al 1993). However, it is unclear whether these Ntransformation processes cause subsoil acidification, as the organisms involved in the N-cycle are either absent or inhibited by soil environmental conditions in the subsoil (Page et al 2002).…”
Section: Subsoil Aciditymentioning
confidence: 99%
“…Secondly, it is unusual that nitrification has not diminished NH 4 + concentrations, given that this usually occurs rapidly in most agricultural soils (Tate 2000). Previous studies of the Warra soil have determined that the reason that nitrification has not diminished NH 4 + concentrations is that the nitrification rate is extremely low (undetectable over a 180-day period), and limited by the lack of an active nitrifying population (Page et al 2002). However, studies have so far failed to determine the original source of the NH 4 + .…”
Section: Introductionmentioning
confidence: 99%